2021
DOI: 10.1155/2021/1058825
|View full text |Cite
|
Sign up to set email alerts
|

Application of Feedforward Neural Network and SPT Results in the Estimation of Seismic Soil Liquefaction Triggering

Abstract: Soil liquefaction is a dangerous phenomenon for structures that lose their shear strength and soil resistance, occurring during seismic shocks such as earthquakes or sudden stress conditions. Determining the liquefaction and nonliquefaction capacity of soil is a difficult but necessary job when constructing structures in earthquake zones. Usually, the possibility of soil liquefaction is determined by laboratory tests on soil samples subjected to dynamic loads, and this is time-consuming and costly. Therefore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…However, the relationship between cyclic shear modulus of soil, number cycle and shear strain, as indicated in this study, has also been outlined in a study by Narepalem and Godavarthi (2019). Other studies have stated the importance of soil evaluation via mathematical models in the design of engineering structure to reduce the impact of liquefaction (Erzin & Tuskan, 2019;Geyin et al, 2020;Pham, 2021;Subedi & Acharya, 2022).…”
Section: Figure 1: Measured and Predicted Cyclic Shear Modulusmentioning
confidence: 70%
See 1 more Smart Citation
“…However, the relationship between cyclic shear modulus of soil, number cycle and shear strain, as indicated in this study, has also been outlined in a study by Narepalem and Godavarthi (2019). Other studies have stated the importance of soil evaluation via mathematical models in the design of engineering structure to reduce the impact of liquefaction (Erzin & Tuskan, 2019;Geyin et al, 2020;Pham, 2021;Subedi & Acharya, 2022).…”
Section: Figure 1: Measured and Predicted Cyclic Shear Modulusmentioning
confidence: 70%
“…Several authors in recent times have equally used mathematical models in the analysis or prediction of factor of safety against soil liquefaction using various input variables such as earthquake magnitude, peak ground acceleration, standard penetration test, saturated unit weight, fines content, depth of ground water level or soil depth, as functional parameters (Erzin & Tuskan, 2019;Geyin et al, 2020;Pham, 2021;Subasi et al, 2021;Subedi & Acharya, 2022). These studies showed the efficacy of mathematical modeling as a powerful tool for rapid and accurate prediction of factor of safety against liquefaction (Erzin andTuskan 2019: Pham, 2021;Subasi et al, &;Katona & Karsa, 2022;Subedi & Acharya, 2022).…”
Section: Figure 2: Measured and Predicted Factor Of Safetymentioning
confidence: 99%
“…Thus, optimization needs to be performed for each model. Among available optimization techniques such as Bayesian optimization and grid search and random search [38][39][40], the random search optimization algorithm is chosen for this study. The next set of hyperparameters is obtained randomly while continuously improving the quality of the features [33].…”
Section: Machine Learning Model Optimization By Hyperparameter Tuningmentioning
confidence: 99%
“…In practice, these evaluations are often based on a combination of eld and laboratory investigation results in addition to liquefaction histories (Seed & Idriss, 1971;Robertson & Fear, 1996;Juang et al, 2000;Idriss & Boulanger, 2006;Boulanger & Idriss, 2016;. To assess soil liquefaction potential, several techniques rely on empirical equations that require determining the cyclic stress ratio based on peak ground acceleration and the cyclic resistance ratio through cyclic laboratory tests (Pham, 2021). However, these techniques are costly due to the need for laboratory experiments and site investigation efforts.…”
Section: Introductionmentioning
confidence: 99%